Analisis Praktik Metode Kitab Al-Jami’ Al-Mukhtasar Min As-Sunan ‘An Rasulillah Wa Ma`rifah As-Shahih Wa Al-Ma’lul Wa Ma ‘Alaihi At-Tarmidzi - Is, Fadhilah (SHAHIH (Jurnal Ilmu Kewahyuan), 2020)
Imam at-Tirmidzi was one of the scholars of the 3rd Hijriyah century who had an amazing sharpness of hadith knowledge. He was born in the Turmuz area. His monumental hadith is J±mi` at-Tarmidz³. There are 10 names that mentioned by scholars in mentioning this book. The J±mi` book covers 48 books which are divided into 2376 chapters, then added with an explanation of `ilal, which covers 3956 hadith. The arrangement of this book is based on the chapter of fiqh, which begins with the at-°ah±rah  book and ends with the al-`il±l book. The compilation of hadith in the chapters is very systematic, comprehensive and practical. He explained the opinion of the mahzab scholars (fiqh) when discussing laws of hadith, so that this book is the main reference in reviewing the diversity of fiqh arguments. Imam at-TirmidzI mentioned new hadith laws terms including; ¥asan  ¡a¥ih, ¡a¥³h ghar³b, ¥asan ghar³b dan ¡a¥ih hasan gharib.. Imam at-Tirmidhi also explained in this book`ilal hadith, ghar³b hadis, jar¥ dan ta`d³l, mukhtalaf ¥adis.